Stories of King Arthur and his Knights - Picard, Barbara Leonie (New York Henry Z. Walck, 1957)
The stories here really do draw you in, as there is more dialogue, and the characters come to life. The volume itself has some beautiful woodcut illustrations by Roy Wood and the type set is exquisite to the eye. They dont seem to make books like these anymore. The prose flows beautifully, capturing the feel of the sources: Malory, the Pearl Poet, the Mabinogion etc., However, the book is aimed directly at readers that are perhaps in early middle school
Keywords: Children Literature